ANTIBIOTIC SENSITIVITY AND MULTIDRUG RESISTANCE TO MICROBIAL ISOLATES FROM FOMITES OF HEALTHCARE WORKERS AT HOLLY MEMORIAL HOSPITAL, OCHADAMU, NIGERIA - Lamidi, Yusuf; Iko-Ojo, Ameh Rufus (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: Microbial contamination of some fomites were screened for, in which over 100 samples were collected from table, mobile phone and biro pen from Holley Memorial Hospital Ochadamu, Kogi State, Nigeria. Methods: Using standard techniques, the samples were collected using a sterile swab stick dipped in normal saline and aseptically swabbing the surface of the fomites. The organisms; Staphylococcus aureus(40%), Escherichia coli (15%), Klebsiella pneumoniae (5%), Pseudomonas aeruginosa (5%), Bacillus cereus (10%), Proteus mirabilis (5%), and Streptococcus pneumoniae(20%) were isolated and identified using both morphological and biochemical techniques. The antibiotic sensitivity test was carried out using disc diffusion method. Results: this finding revealed that all the organisms were sensitive to tarivid but were resistant to septrin with varied zones of inhibition. However, the highest inhibition zone was recorded for perfloxacin (30.00 mm) on Klebsiella pneumoniae. All the isolates showed varying multidrug resistant pattern to the antibiotics used. Conclusion: The understudied fomites are cheap source of nosocomial infections and also showed varying degree of multidrug resistant pattern. Peer Review History: Received: 6 February 2023; Revised: 11 March; Accepted: 25 April 2023, Available online: 15 May 2023 Academic Editor: Dr. Asia Selman Abdullah , Pharmacy institute, University of Basrah, Iraq, asia_abdullah65@yahoo.com Reviewers: Prof. Hassan A.H. Al-Shamahy, Sana'a University, Yemen, shmahe@yemen.net.ye Dr. Ogbonna B. Onyebuchi, Nnamdi Azikiwe University, Awka, Nigeria, summitpharm@yahoo.com